Supporting Transformation of Indonesian Higher Education Quality Assurance: The Advanced Socialization of Merdeka Belajar Policy 26th Chapter - Mochammad Devi Cahya Ruhimat; Yayah Rahyasih; Richard Lionel Gorni; Rifan Shodikin (Universitas Negeri Malang, 2024)
The regulation of the Minister of Education and Culture, Research, Technology, and Higher Education (Permendikbud) Number 53 of 2023 concerning higher education quality assurance standards as the 26th Chapter of the Merdeka Belajar policy, which was officially socialised on August 2023. The Policy is being promoted to encourage quality transformation in Indonesian higher education, which contains several complex reforms and still needs to be better understood by Indonesian higher education stakeholders. Policymakers and implementers in higher education have the potential to make mistakes in following up on this policy. This research aims to formulate a model for advanced socialisation of this Policy, implement it, and report the results. A qualitative, descriptive case study model was used in this research. Selected literature sources from the Scopus database were used to formulate a model of advanced socialisation. The socialisation model as a Webinar was implemented on 6th November 2023 for 838 participants consisting of higher education policymakers, lecturers, students, school principals, and teachers. The evaluation results show that the Webinar's objectives were achieved well, marked by increased participants' understanding. This research recommends continuing dissemination activities to expand and improve knowledge of these transformative policies. As the theoretical implication, this research promotes a new model of socialisation in educational Policy, namely collaborative academic socialisation in higher educational policy.